The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s40243-015-0047-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase change materials (PCMs) integrated into transparent building elements: a review

Abstract: Phase change materials (PCMs) represent an innovative solution that can contribute to the improvement of the energy performance of buildings. Recently a trend towards integrating PCMs into transparent envelope components is observed. This study aims to present the main solutions proposed in the literature for applications in the past few years for PCMs integrated into transparent buildings elements. The temporal development of this application as well as the fundamental principles of its operation is described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 48 publications
0
53
0
Order By: Relevance
“…Microencapsulated phase change materials (MEPCMs) have been recognized as potential energy saving materials because they can be used to reduce the mismatch between heating and cooling demands in buildings (Fokaides et al, 2015, Waqas et al, 2015. For example, an experimental study carried out on a novel translucent full scale passive solar MEPCM wall by Berthou et al (Berthou et al, 2015) revealed that it could be used to provide significant improvement of indoor temperatures in both cold and sunny climates.…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulated phase change materials (MEPCMs) have been recognized as potential energy saving materials because they can be used to reduce the mismatch between heating and cooling demands in buildings (Fokaides et al, 2015, Waqas et al, 2015. For example, an experimental study carried out on a novel translucent full scale passive solar MEPCM wall by Berthou et al (Berthou et al, 2015) revealed that it could be used to provide significant improvement of indoor temperatures in both cold and sunny climates.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many review articles devoted to the description of construction solutions with PCMs and their thermal performance analysis can be found in literature [9,75,[78][79][80][81]83,84,[166][167][168][169][170][171][172][173][174][175][176][177][178][179]. An updated review on PCMs integrated into transparent building elements was recently carried out by Fokaides et al [180]. Cuce and Riffat [181] provided a state-of-the-art review on innovative glazing technologies including those incorporating PCMs.…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…In the study [7], experimental results confirmed supercooling tendencies of calcium chloride hexahydrate (CaCl2.6H2O). Nevertheless, salt hydrates contain nucleating agents which improve nucleating properties and also increase the rate of crystal growth [4]. Nucleating agents can decrease supercooling effect from 20°C to 5°C as is described in [4].…”
Section: Figurementioning
confidence: 99%
“…Nevertheless, salt hydrates contain nucleating agents which improve nucleating properties and also increase the rate of crystal growth [4]. Nucleating agents can decrease supercooling effect from 20°C to 5°C as is described in [4]. Carbon nanofibers, cooper, titanium oxide, potassium sulfate and borax are appropriate nucleating agents as is shown in [12].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation